Immune Response After Cochlear Implantation - Simoni, Edi; Gentilin, Erica; Candito, Mariarita; Borile, Giulia; Romanato, Filippo; Chicca, Milvia; Nordio, Sara; Aspidistria, Marta; Martini, Alessandro; Cazzador, Diego; Astolfi, Laura (Frontiers in Neurology, 2020)
A cochlear implant (CI) is an electronic device that enables hearing recovery in patients with severe to profound hearing loss. Although CIs are a successful treatment for profound hearing impairment, their effectivity may be improved by reducing damages associated with insertion of electrodes in the cochlea, thus preserving residual hearing ability. Inner ear trauma leads to inflammatory reactions altering cochlear homeostasis and reducing post-operative audiological performances and electroacoustic stimulation. Strategies to preserve residual hearing ability led to the development of medicated devices to minimize CI-induced cochlear injury. Dexamethasone-eluting electrodes recently showed positive outcomes. In previous studies by our research group, intratympanic release of dexamethasone for 14 days was able to preserve residual hearing from CI insertion trauma in a Guinea pig model. Long-term effects of dexamethasone-eluting electrodes were therefore evaluated in the same animal model. Seven Guinea pigs were bilaterally implanted with medicated rods and four were implanted with non-eluting ones. Hearing threshold audiograms were acquired prior to implantation and up to 60 days by recording compound action potentials. For each sample, we examined the amount of bone and fibrous connective tissue grown within the scala tympani in the basal turn of the cochlea, the cochleostomy healing, the neuronal density, and the correlation between electrophysiological parameters and histological results. Detection of tumor necrosis factor alpha, interleukin-6, and foreign body giant cells showed that long-term electrode implantation was not associated with an ongoing inflammation. Growth of bone and fibrous connective tissue around rods induced by CI was reduced in the scala tympani by dexamethasone release. For cochleostomy sealing, dexamethasone-treated animals showed less bone tissue growth than negative. Dexamethasone did not affect cell density in the spiral ganglion. Overall, these results support the use of dexamethasone as anti-inflammatory additive for eluting electrodes able to protect the cochlea from CI insertion trauma.